Estimation of Salivary Parameters among Autoimmune Thyroiditis Patients - YASMEEN AMTHUL SYED; BH SATHEESH REDDY; TK RAMAMURTHY; KAVITHA RAJENDRA; NARENDRA KUMAR NERELLA; MEENAKSHI KRISHNAN; MV RAMESH; REZWANA BEGUM MOHAMMED (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Saliva is a complex secretion that protects and lubricates the oral cavity. Various systemic diseases and their treatment alter the salivary gland function; one such disease is Autoimmune Thyroid Disease (AITD). AITD has been postulated to exert its hormonal influence on the salivary glands, leading to reduced salivary output. There’s a paucity of literature, verifying the stated conjunction in human subjects. Aim: The aim was to investigate the salivary profile in AITD patients and its comparison with controls. Materials and Methods: Descriptive cross-sectional comparative study was conducted using convenience sampling method for screening the presence of thyroid disorders. Two groups comprising of 30 patients in each group diagnosed with autoimmune hypothyroiditis (n=30) and hyperthyroiditis (n=30) respectively and thirty healthy volunteers who were age and sex matched were included as controls. Saliva was collected and evaluated for Unstimulated Salivary Flow Rate (USSFR), pH and buffer capacity. ANOVA and Tukey post-hoc test was performed to find the statistical significance and for pairwise comparison. Results:Statistically significant difference was observed between autoimmune hypothyroiditis, autoimmune hyperthyroiditis and control group with respect to USSFR (p<0.007), pH (p<0.001) and buffer capacity (p<0.001). On pairwise comparisons statistically significant difference was observed between autoimmune hypothyroiditis and autoimmune hyperthyroiditis with respect to controls. Conclusion: We conclude that significant involvement of salivary glands may occur in cases of AITD. Our study showed significant reduction of sialometric values in AITD patients when compared to controls. A strong clinical suspicion of thyroid diseases should be considered when there is chronic hyposalivation; hence thyroid profile must also be done, if the known causes have been excluded.